2012
DOI: 10.1007/s13566-012-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Conventional radiation therapy for brain metastases

Abstract: Conventional radiotherapy in the form of whole brain radiation treatment has been a longstanding treatment for brain metastases, and it continues to provide effective palliation as monotherapy and in combination with local and systemic treatments. Advances in systemic therapy have improved survival with metastatic disease, and in those patients with better prognostic factors, more aggressive local therapeutic approaches for brain metastases appear to benefit their survival and intracranial tumor control. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…, and the tumor diameter<4 cm), the results showed that the meso-position lifetime and one-year local control rate in SRS group were superior than WBRT group [19,20]. Chung C, et al indicated that 68% radiation oncologists believed 1-3 brain metastases was ideal quantity to be treated with stereotactic radioactive surgery (SRS) [21]. Murovic Judith, et al made a comparison and analysis on patients with 1-3 brain metastases and on the curative effect for more than patients with 4 brain metastases who only received CK SRS, the results showed that the meso-position OS for both were 13 moths, without apparent difference, therefore CK radiosurgery could effectively control the patients with brain metastases [22].…”
Section: Resultsmentioning
confidence: 99%
“…, and the tumor diameter<4 cm), the results showed that the meso-position lifetime and one-year local control rate in SRS group were superior than WBRT group [19,20]. Chung C, et al indicated that 68% radiation oncologists believed 1-3 brain metastases was ideal quantity to be treated with stereotactic radioactive surgery (SRS) [21]. Murovic Judith, et al made a comparison and analysis on patients with 1-3 brain metastases and on the curative effect for more than patients with 4 brain metastases who only received CK SRS, the results showed that the meso-position OS for both were 13 moths, without apparent difference, therefore CK radiosurgery could effectively control the patients with brain metastases [22].…”
Section: Resultsmentioning
confidence: 99%
“…Chung C et al indicated that 68% of radiation oncologists believed 1-3 brain metastases were ideal quantities to be treated with stereotactic radioactive surgery (SRS) [21]. Murovic Judith et al performed a comparison and analysis on patients with 1-3 brain metastases and on the curative effect for patients with more than 4 brain metastases who only received CK SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Rades Dirk et al performed a retrospective comparison and analysis on patients with brain metastases treated by SRS or WBRT (number of tumours< 3 and tumour diameter < 4 cm), and the results showed that the median survival and one-year local control rate in the SRS group were superior to those in the WBRT group [ 19 , 20 ]. Chung C et al indicated that 68% of radiation oncologists believed 1–3 brain metastases were ideal quantities to be treated with stereotactic radioactive surgery (SRS) [ 21 ]. Murovic Judith et al performed a comparison and analysis on patients with 1–3 brain metastases and on the curative effect for patients with more than 4 brain metastases who only received CK SRS.…”
Section: Discussionmentioning
confidence: 99%
“…Rades Dirk et al performed a retrospective comparison and analysis on patients with brain metastases treated by SRS or WBRT (number of tumours<3 and tumour diameter<4 cm), and the results showed that the median survival and one-year local control rate in the SRS group were superior to those in the WBRT group [19,20]. Chung C et al indicated that 68% of radiation oncologists believed 1-3 brain metastases were ideal quantities to be treated with stereotactic radioactive surgery (SRS) [21]. Murovic Judith et al performed a comparison and analysis on patients with 1-3 brain metastases and on the curative effect for patients with more than 4 brain metastases who only received CK SRS.…”
Section: Discussionmentioning
confidence: 99%